Blood cells diseases and thrombosis - G Leone; S Sica; P Chiusolo; L Teofili; V De Stefano (Haematologica, 2001)
BACKGROUND AND OBJECTIVES: In recent years knowledge about thrombophilia and the mechanisms underlying the pathogenesis of thrombosis has increased greatly. Nevertheless the role of leukocytes and red cells in thrombogenesis is not well established and is probably underestimated. EVIDENCE AND INFORMATION SOURCES: The contribution of leukocytes and red cells to thrombogenesis has been reviewed. Moreover, the prevalence of thrombosis as a complication of hematologic diseases has been examined. The authors are involved in the investigation and management of acute and chronic hematologic diseases as well as in investigation of thrombophilia. Pub-Med was employed as a source of information. STATE OF THE ART: Thrombosis is a major problem in myeloproliferative disorders such as polycythemia vera and essential thrombocythemia. A clonal involvement of megakaryocytopoiesis resulting in elevated levels of platelet-specific proteins, increased thromboxane generation, and expression of activation-dependent epitopes on the platelet surface is regarded as the main origin of thromboembolism; nevertheless, activation of leukocytes and the consequent release of elastase and alkaline phosphatase could play an important role, determining endothelial damage. Thrombosis is a relevant problem in some hemolytic anemias such as paroxysmal nocturnal hemoglobinuria and drepanocytosis. Thrombotic events in hemolytic anemias with membrane defects have been attributed, at least in part, to hypercoagulability related to the exposure of phosphatidylserine of red cell membrane activating plasma prothrombinase and supplying a procoagulant phospholipid anionic surface. A moderate but well-established risk for thrombosis occurs in acute promyelocytic leukemia and acute lymphoblastic leukemia; this risk could be increased by antiblastic drugs affecting the procoagulant activity of cells and the production of coagulation inhibitors from the liver. PERSPECTIVES: Thrombotic complications during hematologic diseases other than thrombophilia due to plasma alteration could be decreased not only by anticoagulant and antiaggregating agents but also by drugs inhibiting activation of leukocytes and red cells and their interaction with platelets.